The Paradigm of Multi-Ethnic-Based Education in Indonesia: An Examination of Entities, Strategies, Models, and Learning Evaluation - Lasaiba, Mohammad Amin; ManArfa, Arman (Universitas Pattimura, 2023)
The paradigm of multicultural education is becoming increasingly important in strengthening cultural, linguistic, and religious diversity in Indonesia. Multicultural education in Indonesia is a form of education that values, respects, and strengthens Indonesia's cultural, linguistic, and religious diversity. To achieve the goals of multicultural education, multicultural teaching strategies and models must be applied, including teaching that values cultural and linguistic diversity, integration of cultural content in learning, empowerment of ethnic groups in learning, and the use of information and communication technology in learning. Evaluating multicultural teaching is also important to ensure the effectiveness of the models and strategies applied. Evaluation can be carried out through several indicators, such as student participation in learning, ability to appreciate cultural and linguistic diversity, and ability to communicate with various ethnic groups